Competitive Intensity As A Quasi Moderator Of The Relationship Between Innovative Efforts And Performance - Perpustakaan UGM, i-lib ([Yogyakarta] : Universitas Gadjah Mada, 2006)
This study empirically investigates the moderating effect of competitive Urrensity on the relationship between innovative efforts and performance. The study proposes that a firm's competitive intensity acts as a quasi-moderator of the relationship between innoVillive dforts and pedbrmance. The results support the predictions of the study. The results indicate that competitive intensity moderates the relationship between innovative efforts and performance such that when competifive intensity is high, the relationship between innovative efforts and performance is positive, and vice versa, when the competitive intensity is low, the relationship between innovative effotis and performance is negative. Furthermore. the results reveal that C0172- petitive inrensity has a positive relationship to the les ei of in erm,ative efforts but has a negative relationship to perjOrtnance.